2015
DOI: 10.1007/s00381-015-2749-8
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous hemorrhages in pediatric supratentorial pilocytic astrocytomas. Malignant presentation of a benign entity

Abstract: The presence of calcifications in the peri-hemorrhagic areas and the presence of mass effect disproportionate to the size of the bleeding are harbingers of the presence of a benign neoplasm that may have bled.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 15 publications
1
6
1
Order By: Relevance
“…Although vascular necrosis and tumor invasion are the primary causes of bleeding in high-grade gliomas, the mechanisms underlying low-grade gliomas remain unclear. [ 2 ] Previous studies have demonstrated that spontaneous bleeding in PAs is due to interaction of different factors, which can be attributed to the specific pathological changes in vascular structures of tumor, such as interstitial degeneration, hyaline degeneration and proliferation of vascular endothelial cells. For instance, the vascular histology of bleeding tumor indicated a poorly developed capillary bed and thin vessel walls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although vascular necrosis and tumor invasion are the primary causes of bleeding in high-grade gliomas, the mechanisms underlying low-grade gliomas remain unclear. [ 2 ] Previous studies have demonstrated that spontaneous bleeding in PAs is due to interaction of different factors, which can be attributed to the specific pathological changes in vascular structures of tumor, such as interstitial degeneration, hyaline degeneration and proliferation of vascular endothelial cells. For instance, the vascular histology of bleeding tumor indicated a poorly developed capillary bed and thin vessel walls.…”
Section: Discussionmentioning
confidence: 99%
“…Occasionally, patients with pilocytic astrocytomas (PAs) may present with a spontaneous intratumoral hemorrhage. [ 2 ] Although there have been few reported cases of spontaneous intracerebral hemorrhage in pediatric cerebellar PAs, such occurrence is extremely rare among elderly patients (Table 1 ). Here, we report a case of an elderly male who presented with cerebellar PAs and spontaneous intratumoral hemorrhage.…”
Section: Introductionmentioning
confidence: 99%
“…[56] Only 6 previous cases of spontaneous hemorrhage into a suprasellar PA have been reported in the pediatric age group. [2] The initial presentation of tumors with hemorrhage is similar to subarachnoid hemorrhage or spontaneous intracranial bleeding and is usually catastrophic. Our patient on the contrary presented with subacute visual decline, memory impairment, and headache over a 1-month period with no history of acute deterioration.…”
Section: Discussionmentioning
confidence: 99%
“…Low-grade gliomas rarely present with hemorrhage, with only 6 cases of spontaneous hemorrhage in pediatric supratentorial PAs having been reported. [2] Radiation therapy (RT)-induced vascular injury is well-documented in these tumors and often occurs within the first decade of the treatment. [3] An immature central nervous system vasculature in the pediatric population may predispose these patients to cerebrovascular morbidity.…”
Section: Introductionmentioning
confidence: 99%
“…It accounts for up to 6–10% of all intracranial hemorrhage. [ 4 ] Large sized tumors in the posterior fossa have a tendency to prolapse into supratentorial cavity following the CSF diversion. The sudden decompression of ventricles precipitates hemorrhage within the tumor that extends through the capsule into fourth ventricle and then to supratentorial ventricles.…”
mentioning
confidence: 99%